Isolation and characterization of biosurfactant Producing bacteria and their application As an antibacterial agent - M.S.RAVAL; S.S.GUND; N.R.SHAH; R.P.DESAI (International Journal of Pharma and Bio Sciences, 2017)
Biosurfactants are the compound which helps in reducing surface tension. These compounds help in stabilizing emulsions, promoting, foaming and reducing surface tension etc. Eight bacterial isolates were isolated from Auranga River, District of Valsad, Gujarat. The isolates were screened for biosurfactant production using different screening methods as oil spreading assay, blood agar hemolysis, emulsification assay, emulsification activity and confirmation by phenol sulfuric method. The biosurfactant was investigated for potential antimicrobial activity by using the cup borer method against Bacillus subtilis, Escherichia coli and Staphylococcus aureus. Antimicrobial studies of the surface active molecules indicated the presence of biocontrolling potential against human bacterial pathogen.